2013
DOI: 10.1177/030089161309900417
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of chemokine serum levels in epithelial ovarian cancer patients

Abstract: The study of serum levels of CCL2/MCP-1, CCL3/MIP-1α, CCL4/MIP-1β, CCL5/RANTES and CXCL8/IL-8 chemokines in epithelial ovarian cancer patients identified a down-regulation in CCL2/MCP-1 and CCL4/MIP-1β, which suggests that the two chemokines may play an important role in the pathophysiology of ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
(25 reference statements)
1
6
0
Order By: Relevance
“…Ding et al [24] noted significantly lower MCP-1 and CCL3 serum concentrations in patients with oral squamous cell carcinoma and leukoplakia. Similar results were obtained for ovarian and colorectal cancer [2527]. Tsaur et al [28] reported down-regulation of MCP-1 and gene expression of other chemokines in renal cell cancer.…”
Section: Discussionsupporting
confidence: 76%
“…Ding et al [24] noted significantly lower MCP-1 and CCL3 serum concentrations in patients with oral squamous cell carcinoma and leukoplakia. Similar results were obtained for ovarian and colorectal cancer [2527]. Tsaur et al [28] reported down-regulation of MCP-1 and gene expression of other chemokines in renal cell cancer.…”
Section: Discussionsupporting
confidence: 76%
“…Compared to healthy controls, both lower levels 28,29 as higher levels of CCL-2 30,31 are reported. Some studies claim that higher levels are associated with advanced disease.…”
Section: Discussionmentioning
confidence: 91%
“…Acts immune suppressive, increases proteolytic activity of cells, adhesion and directly stimulates angiogenesis 44 Inhibits the function of CD8 C cytotoxic T cells and Th1 cells Inhibits the development of M1 macrophages from monocytes and plays an indispensable role in tumor development and progression 45 TGFß1 mRNA expression is an indicator of tumor sensitivity to standard therapy that it can identify biologically aggressive and highly malignant tumors and can predict the prognosis of patients with ovarian cancer 46 Serum level of TGF-b1 has no diagnostic and prognostic role and is associated with sensitivity to standard chemotherapy in ovarian cancer patients 47 CCL-2 /MCP-1 One of the key chemokines that regulate migration and infiltration of monocytes, memory T cells, NKC and DC to sites of inflammation. Has both tumor growth-promoting as growth-inhibiting influences 48,49 Chemotherapy (paclitaxel-carboplatin) can upregulate CCL-2 expression 50 Elevated CCL-2 expression by ovarian cancer cells is reported to be associated both with a better chemotherapy (paclitaxelcisplatin) responses 51 as with chemotherapy resistance 52 CCL-2 levels in serum of ovarian cancer patients compared to healthy controls are both described to be lower 28,29 as higher 30,31 Higher levels are associated with advanced disease 30,31 …”
Section: Tgf-bmentioning
confidence: 99%
“…These results indicated that MIP-1β was necessary and sufficient for the observed increase in tumor adhesion, but an analysis of the current literature did not indicate a clear role for MIP-1β in HGSOC. For example, the concentration of MIP-1β in serum was reported to be lower in HGSOC patients compared to benign patients (38). However, matched ascites and serum samples from HGSOC patients indicated that the concentration of MIP-1β was higher in ascites compared to serum levels (33) suggesting that MIP-1β is concentrated in the peritoneal microenvironment of HGSOC patients.…”
Section: Discussionmentioning
confidence: 99%
“…(B) LP-9 were treated with 10% (v/v) of PBS (Veh) or ascites in SFM in conjunction with an isotype control or MIP-1β blocking antibody for 24 hours, n=3 for each patient sample with OV90 cell line. (C) The Kaplan-Meier plotter tool (38) was utilized with Gene Omnibus and The Cancer Genome Atlas databases to calculate PFS for HGSOC patients with low and high expression of CD24 . (D) Representative omental tissue sections from patients with non-HGSOC or HGSOC conditions stained for P-selectin and calretinin (mesothelial cells).…”
Section: Figurementioning
confidence: 99%